2018
DOI: 10.1016/j.cellsig.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 plays a role in CXCL12 but not CCL3-induced chemotaxis and Rac1 GEF inhibitor NSC23766 has off target effects on CXCR4

Abstract: Cell migration towards a chemotactic stimulus relies on the re-arrangement of the cytoskeleton, which is triggered by activation of small G proteins RhoA, Rac1 and Cdc42, and leads to formation of lamellopodia and actin polymerisation amongst other effects. Here we show that Rac1 is important for CXCR4 induced chemotaxis but not for CCR1/CCR5 induced chemotaxis. For CXCL12-induced migration via CXCR4, breast cancer MCF-7 cells are reliant on Rac1, similarly to THP-1 monocytes and Jurkat T-cells. For CCL3-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The SDF‐1/CXCR4 signaling pathway participates in metastatic process in many cancer types such as liver cancer, colorectal cancer and breast cancer 35 . CXCR4 is widely expressed in CD43 + cancer stem cells and SDF‐1 is widely expressed in tumor endothelial cells 36 . Therefore, CXCR4 + tumor stem cells can migrate or invade along the SDF‐1 concentration gradient to seed in distant tissues or organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDF‐1/CXCR4 signaling pathway participates in metastatic process in many cancer types such as liver cancer, colorectal cancer and breast cancer 35 . CXCR4 is widely expressed in CD43 + cancer stem cells and SDF‐1 is widely expressed in tumor endothelial cells 36 . Therefore, CXCR4 + tumor stem cells can migrate or invade along the SDF‐1 concentration gradient to seed in distant tissues or organs.…”
Section: Discussionmentioning
confidence: 99%
“…35 CXCR4 is widely expressed in CD43 + cancer stem cells and SDF-1 is widely expressed in tumor endothelial cells. 36 Therefore, CXCR4 + tumor stem cells can migrate or invade along the SDF-1 concentration gradient to seed in distant tissues or organs. CXCR4 has also been reported to promote the progression of tumors, and the overexpression of CXCR4 has been proved to correlated with poorer prognosis and shorter survival time.…”
Section: Parametersmentioning
confidence: 99%
“…Recent studies have also demonstrated the potential of NSC23766 in combination therapy to overcome resistance to targeted as well as cytotoxic therapies (Karpel-Massler et al, 2017;Tian et al, 2018). Nonetheless, although the use of NSC23766 may look promising in some instances, the high effective concentrations (µM range) and the reported off-target effects in platelets, on alfa-1-adrenergic receptors and CXCR4 chemokine receptors, limits its therapeutic use (Dutting et al, 2015;Mills et al, 2018;Yu et al, 2019).…”
Section: Targeting Tiam1mentioning
confidence: 99%
“…This inhibitor shows dual secondary effects on the CXCR4 signaling. It acts as an activator in cAMP assays whereas it is inhibitory in migration and calcium release assays [ 101 ]. Another study showed that heregulin, a ligand for Erb3 and Erb4 receptors, sensitizes breast cancer cells for CXCL12 mediated Rac1 activation.…”
Section: The Cxcl12/cxcr4 Pathway Induces Breast Cancer Motilitymentioning
confidence: 99%